Exploring the meaning of cancer in the lives of higher education teachers - Jordan, Henry H., III, author; Foster, Ann, advisor; Albright, Len, committee member; Banning, Jim, committee member; Oltjenbruns, Kevin Ann, committee member (Colorado State University. Libraries, 2005)
The purpose of this study was to examine the meaning of cancer from the viewpoint of higher education teachers who had experienced cancer. Types of cancer included prostate, thyroid, breast, colon, and ovarian. The participants ranged in age from 48 to 65 years. Years teaching since diagnosis ranged from 2 to 20 with a total of 43 years. The current health status of the participants ranged from good to excellent. A qualitative approach was used to gather information from 9 higher education teachers. All 9 participants were currently teaching at local colleges and universities in Atlanta. A series of semi-structured, face-to-face in-depth interviews were conducted with each participant and the data were recorded and transcribed verbatim. The interviews followed a five-question interview guide. The first question asked about the diagnosis and prognosis, while the remaining four questions focused on cancer and its effect on one's professional life. The researcher, also a cancer survivor, invited the participants to openly share their cancer journeys. The resulting data were analyzed using the constant comparative method of data analysis and interpretation. From the analysis three major themes emerged: (1) the nature of cancer, (2) dealing with cancer, and (3) the outcomes of cancer. Each major theme has three sub themes. Connecting the major themes was the concept of time, both chronological and phenomenological. The participants worked to understand their disease as well as how the disease affected them. Several participants viewed cancer as a major life-changing experience, while others minimized the life changing effects. From the participants' words, a description of their survival experiences resulted. The study concludes with practical advice from the participants for others who face cancer or are interested in learning about these life experiences.
Keywords: higher education; oncology; families and family life; personal relationships; sociology; individual and family studies